2016
DOI: 10.1111/1742-6723.12542
|View full text |Cite
|
Sign up to set email alerts
|

Understanding drivers of Demand for Emergency Service Trends in Years 2010–2014 in New South Wales: An initial overview of the DESTINY project

Abstract: The elderly population had the highest rate of ED attendances. The use of diverse diagnosis classifications and source information systems may present problems with further analysis. Patterns and characteristics of ED presentations in NSW were broadly consistent with those reported in other states in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 20 publications
3
67
0
1
Order By: Relevance
“…Presenting problem categories were defined using the original derivation data classification 2. Data were collected on consecutive patients during allocated research hours (Monday to Friday between 10:00 and 21:00) by a trained research nurse who observed each triage and who was unaware of START score calculations or the eventual disposition of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Presenting problem categories were defined using the original derivation data classification 2. Data were collected on consecutive patients during allocated research hours (Monday to Friday between 10:00 and 21:00) by a trained research nurse who observed each triage and who was unaware of START score calculations or the eventual disposition of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…This was a retrospective data analysis of State-wide Emergency Department data and undertaken as part of the Demand for Emergency Services Trend in Years 2010–15 (DESTINY) study [7]. …”
Section: Methodsmentioning
confidence: 99%
“…Data collection includes, referral source (self-referred, General Practice, Specialist, Nursing Home), mode of arrival (self-referral, Ambulance), hospital facility, triage category (Australasian Triage Scale) [9], presenting problem, mode of separation (admitted to hospital, discharged or died). Presenting problems allocated by triage nurses at the point of patient arrival to ED were categorised into broad clinical groups and described elsewhere (see Table 1) [7]. For example, neurological complaints included headache, dizziness, weakness and ataxia), respiratory complaints included shortness of breath, cough and wheeze and cardiovascular complaints included chest pain and palpitations.…”
Section: Methodsmentioning
confidence: 99%
“…This was a retrospective, ecological time series analysis for the majority of ED presentations in NSW, Australia, over five calendar years, 2010–2014 . NSW is the most populous state in Australia, with a combined urban and rural population of 7.5 million over 800 000 square kilometres.…”
Section: Methodsmentioning
confidence: 99%
“…Individual, non‐identified, ED clinical information came from the NSW ED Data Collection database. Exclusion criteria were hospitals not submitting data for the entire study period, planned presentations, dead on arrival and transfers from other facilities . Time series were prepared of the weekly proportion of ED presentations that left the ED in >4 h of arrival, and of patients that departed the ED without waiting to be seen or that departed at their own risk before completing treatment (‘did not wait’).…”
Section: Methodsmentioning
confidence: 99%